What is right for you?. (2nd February 2022) - Bradbury, Aaron
Abstract : There are many routes into becoming qualified in the early years. There is a national standard in England and similar requirements in other parts of the United Kingdom. These differ and so it is important that you know the requirements within the career framework that is relevant to your setting.